Alcohol-associated liver disease: A review - Damarla Nagarjuna; Elumalai Karthikeyan (Gastroenterology & Endoscopy)
Alcohol-associated Liver Disease (ALD) is a collection of liver disorders caused by prolonged and excessive alcohol consumption, ranging from fatty liver alterations to fibrosis and cirrhosis. This condition accounts for 5.9 ​% of all annual fatalities, making it a significant contributor to the global disease burden. The pathophysiology of ALD involves various processes, such as abnormal alcohol metabolism, inflammation, oxidative stress, and disrupted lipid metabolism. Risk factors for ALD include obesity, metabolic syndrome, hepatitis, smoking, and sex, with women being more susceptible to liver damage at lower levels of alcohol consumption. To prevent advanced ALD and promote recovery, prompt intervention and alcohol abstinence are essential. However, diagnosing ALD can be challenging owing to the lack of early symptoms, emphasising the need for effective and accessible treatments. Current treatments for ALD focus on symptomatic management and liver transplantation in end-stage cases. However, the limited number of donors and the requirement for alcohol abstinence before transplantation pose significant challenges. Understanding the molecular mechanisms underlying ALD is crucial for the identification and development of novel therapeutic strategies. This review aims to provide an overview of the pathophysiology, diagnosis, and treatment of ALD, highlighting the critical need for further research and interventions to address this global health threat.